Identification Of Students' Misconceptions And Information Sources Using The Five-Tier Diagnostic Test Model Fluid Dynamic Concept - Harita, Taufik Hidayat; Pardede, Hebron; Marbun, Juliaster; Silaban, Bajongga; Silaban, Irving Josafat Alexander (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
One of the main issues in physics education is the high incidence of student misconceptions, particularly regarding the concept of dynamic fluids. Misconceptions can hinder conceptual understanding and negatively affect students’ cognitive abilities in comprehending more advanced material. This study aims to identify the level of misconceptions and determine the sources of information that contribute to the formation of these misconceptions. The research employed a descriptive quantitative approach using the Five-Tier Diagnostic Test instrument, which consists of five components: answer selection, confidence in the answer, reasoning, confidence in the reasoning, and source of information. The research subjects were all 19 eleventh-grade students of SMA Swasta Methodist 7 Medan in the 2024/2025 academic year. The results showed that 12% of the students experienced misconceptions, with the most dominant subtopic being the continuity equation (14%). The primary sources of misconceptions were identified as personal reasoning (25%) and peer interaction (20%). These findings indicate that both internal and social factors significantly influence the development of incorrect conceptual understanding. Therefore, the use of a five-tier diagnostic instrument is recommended as an early identification tool to design more effective and targeted learning improvement strategies.